Antiatherosclerotic Effect of Canarium odontophyllum Miq. Fruit Parts in Rabbits Fed High Cholesterol Diet. (1st July 2012) - Shakirin, Faridah Hanim; Azlan, Azrina; Ismail, Amin; Amom, Zulkhairi; Yuon, Lau Cheng
Abstract : The effect of C. odontophyllum (CO) fruit parts was investigated in hypercholesterolemic rabbits. Forty-nine rabbits, which were randomly divided into seven groups of seven animals (n = 7 ), received a diet containing different parts of CO fruit parts for 8 weeks. The groups were as follows: (1) normal diet: NC group and (2) hypercholesterolemic diet: PC, HS (10 mg/kg/day simvastatin), HPO (20 g kg −1 oil extracted from the pulp of CO), HKO (20 g kg −1 oil extracted from the kernel of CO), HF (50 g kg −1 fullfat pulp of CO), and HD (50 g kg −1 defatted pulp of CO). Among these groups, rabbits receiving defatted pulp of CO showed the greatest cholesterol lowering effect as it had reduced plasma LDL-C, TC, and thiobarbiturate reactive substance (TBARS) levels as well as atherosclerotic plaques. The presence of high dietary fiber and antioxidants activity are potential factors contributing to the cholesterol lowering effect. Consequently, these results indicate the potential use of CO defatted pulp as a cholesterol lowering and antioxidant agent.